2022
DOI: 10.1002/brb3.2853
|View full text |Cite
|
Sign up to set email alerts
|

Effects of online brain training on self‐reported mental health symptoms for generally healthy adults during the Covid‐19 pandemic

Abstract: Background: The cognitive training Strategic Memory Advanced Reasoning Training (SMART) has been shown to improve symptoms of depression, anxiety, and stress when completed using in-person delivery, but mental health outcomes have not yet been studied for online delivery of SMART. Methods: Data was analyzed from 145 generally healthy adults participating in the BrainHealth Project pilot study who had access to 12 weeks of online self-paced SMART and self-reported mental health symptoms on the Depression Anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Insel claims we are not in a mental illness crisis but rather in a crisis of mental health care . We agree with this viewpoint and add that the solutions are also cognitive ( Venza et al, 2016 ; Han et al, 2018 ; Chapman et al, 2021 ; Laane et al, 2022 ). We propose that capacity-building protocols may help to protect against and even intercept mental health issues by giving individuals the tools to be agents of change by drawing upon their internal resources.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Insel claims we are not in a mental illness crisis but rather in a crisis of mental health care . We agree with this viewpoint and add that the solutions are also cognitive ( Venza et al, 2016 ; Han et al, 2018 ; Chapman et al, 2021 ; Laane et al, 2022 ). We propose that capacity-building protocols may help to protect against and even intercept mental health issues by giving individuals the tools to be agents of change by drawing upon their internal resources.…”
Section: Introductionsupporting
confidence: 67%
“…In prior work, we have shown that participants, outside of aggregate settings such as workplace or group contexts, significantly improved their brain skills across multiple domains of intellect, wellbeing, social connectedness, and real-life responsibilities ( Chapman et al, 2015 ; Venza et al, 2016 ; Chapman et al, 2021 ; Laane et al, 2022 ). This work has led to development and testing of validated BrainHealth Index that can be used to evaluate improved brain health over time, regardless of intervention.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation